1999
DOI: 10.1016/s1074-5521(99)80072-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel nonsecosteroidal vitamin D mimics exert VDR-modulating activities with less calcium mobilization than 1,25-dihydroxyvitamin D3

Abstract: These novel VDR modulators may have potential as therapeutics for cancer, leukemia and psoriasis with less calcium mobilization side effects than are associated with secosteroidal 1,25(OH)2D3 analogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 28 publications
3
111
0
4
Order By: Relevance
“…This phenomenon has been observed in the case of vitamin D receptor (VDR) ligands, where potent VDR agonists did not displace radiolabeled 1,25-dihydroxyvitamin D3 because of its high K on and low K off for the receptor (Boehm et al, 1999;Ma et al, 2006). Our biochemical AlphaScreen-based assays using purified LXR␣ and ␤ LBD proteins and synthetic cofactor LXXLL motif peptide (SRC-2 NR box III) clearly demonstrate that 5,6-EC is bona fide ligand of both LXR␣ and ␤ subtypes, with at least a single-digit micromolar potency (Fig.…”
Section: Abca1 Abcg1mentioning
confidence: 87%
“…This phenomenon has been observed in the case of vitamin D receptor (VDR) ligands, where potent VDR agonists did not displace radiolabeled 1,25-dihydroxyvitamin D3 because of its high K on and low K off for the receptor (Boehm et al, 1999;Ma et al, 2006). Our biochemical AlphaScreen-based assays using purified LXR␣ and ␤ LBD proteins and synthetic cofactor LXXLL motif peptide (SRC-2 NR box III) clearly demonstrate that 5,6-EC is bona fide ligand of both LXR␣ and ␤ subtypes, with at least a single-digit micromolar potency (Fig.…”
Section: Abca1 Abcg1mentioning
confidence: 87%
“…This cell context-selective action translated into reduced hypercalcemia in vivo in comparison with 1,25-(OH) 2 D 3 when mice were treated orally or topically with the VDRMs LY2108491 and LY2109866 ( Figures 9 and 11 and Table 1). Although nonsecosteroidal and nonsteroidal VDR ligands have been described (24,38,39), they have not been shown to act as a modulator in a cell context-dependent manner. Recently, a tissue-and cell type-selective secosteroidal VDRM (Ro-26-9228) has been described (40).…”
Section: Discussionmentioning
confidence: 99%
“…EB1089 effectively inhibits the growth of LNCaP cells, exhibits greater potency than 1,25(OH) 2 D 3 (Skowronski et al, 1995), and is only 50% as calcemic in vivo (Hansen and Maenpaa, 1997;Kissmeyer et al, 1997). Other analogs, including 16-diene analogs (Schwartz et al, 1994;Hedlund et al, 1997), 1,25 dihydroxy-16-ene-23-yne-vitamin D 3 (Schwartz et al, 1995), 19-nor-hexafluoride D 3 analogs (Campbell et al, 1997), 19-nor-26,27-bishomo-vitamin D 3 analogs (Kubota et al, 1998), 20-cyclopropyl-cholecalciferol vitamin D 3 (Koike et al, 1999), 5,6-trans-16-ene-vitamin D 3 (Hisatake et al, 1999), and some nonsecosteroidal analogs (Boehm et al, 1999) also inhibit the growth of prostate cancer cells in vitro. Interestingly, some analogs inhibit the growth of the 1,25(OH) 2 D 3 resistant DU145 cells (Schwartz et al, 1994;Kubota et al, 1998;Koike et al, 1999), and it has been suggested that DU145 resistance to 1,25(OH) 2 D 3 is due to the rapid metabolism of 1,25(OH) 2 D 3 by 24-hydroxylase in these cells (Ly et al, 1999).…”
Section: Vitamin D Analogsmentioning
confidence: 99%